FLZ attenuates Parkinson's disease pathological damage by increasing glycoursodeoxycholic acid production via down-regulating Clostridium innocuum - Meiyu Shang; Jingwen Ning; Caixia Zang; Jingwei Ma; Yang Yang; Yueqi Jiang; Qiuzhu Chen; Yirong Dong; Jinrong Wang; Fangfang Li; Xiuqi Bao; Dan Zhang (Acta Pharmaceutica Sinica B)
Increasing evidence shows that the early lesions of Parkinson's disease (PD) originate from gut, and correction of microbiota dysbiosis is a promising therapy for PD. FLZ is a neuroprotective agent on PD, which has been validated capable of alleviating microbiota dysbiosis in PD mice. However, the detailed mechanisms still need elucidated. Through metabolomics and 16S rRNA analysis, we identified glycoursodeoxycholic acid (GUDCA) was the most affected differential microbial metabolite by FLZ treatment, which was specially and negatively regulated by Clostridium innocuum, a differential microbiota with the strongest correlation to GUDCA production, through inhibiting bile salt hydrolase (BSH) enzyme. The protection of GUDCA on colon and brain were also clarified in PD models, showing that it could activate Nrf2 pathway, further validating that FLZ protected dopaminergic neurons through promoting GUDCA production. Our study uncovered that FLZ improved PD through microbiota–gut–brain axis, and also gave insights into modulation of microbial metabolites may serve as an important strategy for treating PD.